2021
DOI: 10.1016/s1473-3099(21)00146-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of different sampling approaches for SARS-CoV-2 RT-PCR testing: a systematic review and meta-analysis

Abstract: Background The comparative performance of different clinical sampling methods for diagnosis of SARS-CoV-2 infection by RT-PCR among populations with suspected infection remains unclear. This meta-analysis aims to systematically compare the diagnostic performance of different clinical specimen collection methods. Methods In this systematic review and meta-analysis, we systematically searched PubMed, Embase, MEDLINE, Web of Science, medRxiv, bioRxiv … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
198
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(208 citation statements)
references
References 78 publications
6
198
2
2
Order By: Relevance
“…Since it contains, e.g., hormones, growth factors, enzymes, antibodies as well as microbes and their products, it might be useful in the early detection of systemic diseases, like cancer, autoimmune disorders, cardiovascular disease, diabetes, or virus-related diseases (7,8). The diagnostic potential for saliva in ambulatory care and under self-collection conditions has recently been summarized in a meta-analysis for SarS-CoV-2 RT-PCR testing (9).…”
Section: Introductionmentioning
confidence: 99%
“…Since it contains, e.g., hormones, growth factors, enzymes, antibodies as well as microbes and their products, it might be useful in the early detection of systemic diseases, like cancer, autoimmune disorders, cardiovascular disease, diabetes, or virus-related diseases (7,8). The diagnostic potential for saliva in ambulatory care and under self-collection conditions has recently been summarized in a meta-analysis for SarS-CoV-2 RT-PCR testing (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although paired comparison between different swab samples lacked in this study, our study demonstrated that anterior nasal samples provided a lower antigen test sensitivity than our previous study evaluating nasopharyngeal samples 3 . Nevertheless, this lower sensitivity of 72.5% may be acceptable since according to the reported systematic review, sensitivity of nasal swab was 86% in comparison to nasopharyngeal swab by RT-PCR 9 . The sensitivity of antigen tests is largely influenced by the viral load in collected samples 10 13 .…”
Section: Discussionmentioning
confidence: 92%
“…The elimination criteria were as follows: (1) duplicate studies; (2) studies in which the experimental group was subjected to other TCM therapies, such as acupuncture, moxibustion, cupping, massage, qigong, and taiji therapy, in addition to the CWM; (3) studies in which the control group was treated with a form of TCM or integrated medicine; (4) studies in which data could not be extracted.…”
Section: Study Elimination Criteriamentioning
confidence: 99%
“…Since the occurrence of the novel coronavirus pneumonia (NCP) in December 2019, the situation has increasingly become severe, and the disease continues to spread, which has had a significant impact on health and lives of people (1). Coronavirus disease 2019 (COVID-19) is a highly contagious viral pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (2). People are usually susceptible to SARS-CoV-2, and there are different clinical manifestations (3).…”
Section: Introductionmentioning
confidence: 99%